The effect of FeNi-AlN layer thickness on the response of magnetic SAW sensor by FEM simulation - Phu, Do Duy; Hoang, Hong Si; Van Vinh, Le (Bulletin of Electrical Engineering and Informatics, 2024)
In this study, we used simulation to investigate the optimal working point of a surface acoustic wave-magnetostriction sensor by varying the thickness of the magnetic sensitive layer using the finite elements method. We evaluated the sensor’s sensitivity by simulating the responses at the optimal point and changing the thickness of the magnetic sensitive layer (h3). Additionally, we reduced the piezoelectric substrate thickness (h1) at the optimal point to determine the limit point of the center frequency (f0) and improve the sensor sensitivity for low magnetic field intensity measurements by performing a wavelength reduction (λ). For the simulation, we selected a delay-line FeNi/IDT/AlN structure with specific materials and electrode parameters. Our results show that the optimal structure of the sensor is at h1=400 μm, λ=40 μm, and h3=1,060 nm, with a maximum f0 of 140.38493 MHz and maximum surface acoustic wave velocity of 5,615.4 m/s. At this optimal structure, the sensitivity reaches the maximum value of 10.287 kHz/Oe with a working range from 0 to 89 Oe. We also found that reducing the piezoelectric substrate thickness to 35 μm significantly reduces the manufacturing and simulation time, but the frequency response cannot determine the center frequency.